2018
DOI: 10.32598/hdq.3.4.185
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Professional Competency of Iranian Preschool Administrators Based on Crisis Management Approach

Abstract: Background: Children's inability to protect themselves, shows the importance of crisis management in preschool period. Preschool administrators can help them with the risk prevention during crisis. We aimed to investigate the professional competencies of preschool administrators based on crisis management approach. Materials and Methods:The study participants included 387 preschool administrators in Tehran, Iran, selected by multi-stage cluster sampling method. The surveying tool was a questionnaire designed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…For this purpose, relevant experts and prepared checklists can be used to assess the safety of public places and health care facilities like hospitals and also infrastructure readiness [26,27]. It is also necessary to evaluate the occupational competencies of managers in crisis management [28]. It can be certainly said that teaching people and improving their knowledge and attitude regarding health in accidents and disasters result in maintaining health and safety in the therapeutic centers for children and people with disabilities [27].…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, relevant experts and prepared checklists can be used to assess the safety of public places and health care facilities like hospitals and also infrastructure readiness [26,27]. It is also necessary to evaluate the occupational competencies of managers in crisis management [28]. It can be certainly said that teaching people and improving their knowledge and attitude regarding health in accidents and disasters result in maintaining health and safety in the therapeutic centers for children and people with disabilities [27].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the findings of these studies showed that the research on crisis management at the Iranian schools was very poor and most of them emphasized that students, teachers, and principals should be trained for crisis management and confrontation with it. In addition, it is necessary to evaluate the professional competence of principals in crisis management [19]. It is recommended that we take significant steps in elevating the confrontation and intervention level of crisis through the evaluation and improvement of safety cultural level.…”
Section: Mostafavi Darani and Colleaguesmentioning
confidence: 99%
“…Therefore, organizations try to attract, by training, and try to keep successful administrators in promoting the organization ( 3 ). Administrators are people who influence the future of the organization and their competence and decisions are effective in managing the organization and its successful achievements ( 4 ). Therefore, in order to achieve the desired results and efficient management of the organization, administrators must be aware of new challenges such as advances in communications and information technology, increasing competition due to globalization and the strategic importance of management perspective and reveal the potential talents of individuals ( 5 ).…”
Section: Introductionmentioning
confidence: 99%